2019
DOI: 10.3382/ps/pey423
|View full text |Cite
|
Sign up to set email alerts
|

Changes to mineral levels in the yolk of meat chicken embryos during incubation

Abstract: A total of 864 settable Cobb 500 eggs were used to explore changes in yolk mineral content during incubation. Eggs were individually weighed and then placed in a commercial incubator. On embryonic day (ED) 0, 6.5, 13.5, and 17.5, 36 eggs were sampled and yolk weight and mineral content were determined. The concentration of iron (Fe), phosphorus (P), and zinc (Zn) declined (P < 0.05) from ED0 to ED17.5. The concentration of calcium (Ca), magnesium (Mg), and strontium (Sr) increased (P < 0.05) from ED0 to ED17.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 22 publications
2
23
0
Order By: Relevance
“…The mineral content of the samples was measured using the method of Hopcroft, Cowieson, Muir, & Groves [26] . Briefly, 1 g of sample was homogenized in a tissue grinding tube (YJQ, Solarbio, Beijing, China) and then freeze-dried.…”
Section: Methodsmentioning
confidence: 99%
“…The mineral content of the samples was measured using the method of Hopcroft, Cowieson, Muir, & Groves [26] . Briefly, 1 g of sample was homogenized in a tissue grinding tube (YJQ, Solarbio, Beijing, China) and then freeze-dried.…”
Section: Methodsmentioning
confidence: 99%
“…The amount of minerals in yolk reflects that the uptake content and enrichment can have beneficial effects [113]. In-ovo supplementation of minerals has improved bone properties and development in hatchlings and mature broilers [113,114,115].…”
Section: Effects Of Dietary ω-3 and ω-6 Fatty Acids On Bonesmentioning
confidence: 99%
“…Fatty acid supplementation, especially of ω-3 and ω-6, helps in improving fertility, semen quality and quantity. Kelso et al [114] found that dietary fish oil or corn oil supplementation to chickens at a level of 50 g/kg in their diet led to significantly higher (96%) fertility rates than the rates prior to supplementation (89%). Kelso et al [115] noticed that the supplementation of ALA in male diets led to higher fertility at 39 weeks of age because of the increased ω-3 fatty acid proportion in the phospholipids of sperm.…”
Section: Improved Fertility Rates and Semen Qualitymentioning
confidence: 99%
“…Development and growth of poultry embryos are dependent upon the nutrient deposits in the eggs [19]. The yolk sac provides the chicken embryo with essential minerals nutrients for embryonic growth [20,21]. Zinc is an essential nutrients required in small amounts for normal growth and development of the avian embryo functioning as catalytic or structural cofactors in metal-containing enzymes [1].…”
Section: Discussionmentioning
confidence: 99%